FACTORS IMPACTING ON SUSTAINABLE LAND REFORM IN THE EHLANZENI DISTRICT, MPUMALANGA - ARCHARY, LEONA CASSANDRA (My University, 2014)
The Freedom Charter states “restrictions of land ownership on a racial basis shall be ended, and all land be re-divided amongst those who work it to banish famine and land hunger. The State shall help the peasants with implements, seed, tractors and dams to save the soil and assist the tillers.” With the advent of democracy in South Africa, land became one of the key issues of the negotiated settlement of 1994 and the government adopted a strategy to reverse the racially skewed land ownership patterns that had been created by the apartheid regime. However, the redistribution programme one of the key programmes utilised, has been widely criticised for its lack of support to new black farmers and its contribution to job losses and food insecurity. The majority of farms acquired since 1994 appear to be unproductive and lying fallow. Although a number of reasons are given for the collapse of land reform projects, this research was aimed at gaining a deeper understanding of the different factors impacting on sustainability of the land redistribution programme. The qualitative research methodology was used in the research to identify and examine the factors impacting on the performance of land redistribution in the Ehlanzeni District. Four projects completed through the redistribution programme in the Ehlanzeni District of the Mpumalanga Province were selected. The research found that the key factors affecting sustainability of projects in the Ehlanzeni District include gaps within the policy and redistribution programme, lack of capacity of the state machinery to deliver, poor institutional arrangements that do not allow for beneficiary participation and integration across all sectors involved in land issues, poor or limited support provided to new farmers, and poor planning from the inception of ii projects. There is lack of a “master plan” that directs land acquisition to ensure that it addresses the needs of the participants in the programme. A 10-step plan to address some of the challenges raised above is proposed. The plan would allow for a more detailed profiling of the area as well as the needs of the beneficiaries to enhance planning and land acquisition. It would also ensure greater collaboration among stakeholders for improved support. The plan includes a clear integration of the principles of improved monitoring so as to ensure that all partners in the process act effectively against their mandate.
MM (P&DM) thesis
Keywords: Land reform